Impact of the COVID-19 pandemic on lung cancer diagnosis in northern Poland-addressing the COVID-19 debt. - Anna Romaszko-Wojtowicz; Anna Doboszyńska; Anna Piechnik; Krzysztof Kuziemski; Dariusz Szplit; Szczepan Cofta; Katarzyna Glińska-Lewczuk (PLoS ONE)
Introduction Lung cancer, one of the leading causes of death due to neoplasms, requires prompt diagnosis and immediate treatment. The COVID-19 pandemic affected healthcare systems worldwide, having adverse effects on all aspects, particularly on the fate of patients with suspected neoplastic diseases. Limited access to healthcare, disruptions in regular operations (reassigning roles to some wards), postponed hospital admissions, prolonged diagnostic processes, and other factors have collectively led to the phenomenon known as COVID-19 debt. Material and methods A retrospective analysis covered statistical data concerning the diagnosis of lung cancer obtained from three centres in northern Poland (Olsztyn, Bydgoszcz, Gdansk) and concerning years 2016 to 2022. Relative risks (RR) with 95% confidence intervals (CI) for cancer event were calculated. Before the pandemic, these centers prioritized the diagnosis of suspected lung cancer cases, which was subsequently disrupted during the pandemic due to various factors. Results The COVID-19 pandemic led to a decrease in diagnosed lung cancer cases, especially in hospitals repurposed for COVID-19 care. A statistically significant trend in lung cancer incidence per 100,000 inhabitants was observed specifically in healthcare centers that maintained normal operations without disruption. Conclusion The concept of the COVID debt helps explain changes in lung cancer diagnosis during and post-pandemic, highlighting the need for increased public awareness and intensified diagnostic efforts to facilitate earlier disease detection.